Review of "Identity and Indiscernibility in Quantum Mechanics" - Dewar, Neil (Filozofia Nauki, 2022)
Tomasz Bigaj’s new book is an authoritative and comprehensive discussion of recent issues concerning the means and metaphysical implications of individuating identical quantum particles. This review briefly summarises the book’s contributions and considers some of its implications for the debate over indiscernibility in quantum mechanics.